HLA Desensitization in Solid Organ Transplantation: Anti-CD38 to Across the Immunological Barriers - Joher, Nizar; Matignon, Marie; Grimbert, Philippe (Frontiers in Immunology, 2021)
The presence of anti-human leucocyte antigen (HLA) antibodies in the potential solid organ transplant recipient’s blood is one of the main barriers to access to a transplantation. The HLA sensitization is associated with longer waitlist time, antibody mediated rejection and transplant lost leading to increased recipient’s morbidity and mortality. However, solid organ transplantation across the HLA immunological barriers have been reported in recipients who were highly sensitized to HLA using desensitization protocols. These desensitization regimens are focused on the reduction of circulating HLA antibodies. Despite those strategies improve rates of transplantation, it remains several limitations including persistent high rejection rate and worse long-term outcomes when compare with non-sensitized recipient population. Currently, interest is growing in the development of new desensitization approaches which, beyond targeting antibodies, would be based on the modulation of alloimmune pathways. Plasma cells appears as an interesting target given their critical role in antibody production. In the last decade, CD38-targeting immunotherapies, such as daratumumab, have been recognized as a key component in the treatment of myeloma by inducing an important plasma cell depletion. This review focuses on an emerging concept based on targeting CD38 to desensitize in the field of transplantation.